Assistant Competency Exam Preparation Training Assistance Health Workers in the Pharmacy Sector at SMK Kesehatan Surabaya - Wibowo, Teguh Setiawan; Ngete, Ani Florida (Asian Journal of Community Services, 2024)
In health services provided by pharmaceutical personnel, the health workers are assisted in carrying out their duties by the assistant health workers who must have a minimum secondary education qualification in the health sector and must be under the supervision of health workers. However, it does not require a registration certificate or practice permit. The method used theoretical presentation, question/answer, practice and offline assistance at SMK Kesehatan Surabaya Laboratory. The results are the accompanying training activity to prepare the competency exam for assistant health workers in the field of Pharmacy at SMK Kesehatan Surabaya received a positive response and the participants were very enthusiastic. It is hoped that the pharmacy assistant health worker competency exams carried out at SMK Kesehatan Surabaya will be more in collaboration with related institutions such as BNSP which are recognized for their professionalism to support increasing understanding, technical skills and quality of SMK Kesehatan Surabaya students.